2018
DOI: 10.1136/postgradmedj-2018-135719
|View full text |Cite
|
Sign up to set email alerts
|

Clocks in the clinic: circadian rhythms in health and disease

Abstract: Circadian rhythms are endogenously generated recurring patterns of around 24 hours with well-established roles in physiology and behaviour. These circadian clocks are important in both the aetiology and treatment of various psychiatric and metabolic diseases. To maintain physiological homeostasis and optimal functioning, living life synchronised to these clocks is desirable; modern society, however, promotes a ‘24/7’ lifestyle where activity often occurs during the body’s ‘biological night’, resulting in misti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 84 publications
(53 reference statements)
0
25
0
Order By: Relevance
“…Aging is accompanied by an increase in other noncommunicable diseases such as type 2 diabetes, cardiovascular disease, and cancer [8], which have also been suggested to involve circadian and 24-h activity rhythm disturbances [1,50].…”
Section: -H Activity Rhythms and Other Age-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is accompanied by an increase in other noncommunicable diseases such as type 2 diabetes, cardiovascular disease, and cancer [8], which have also been suggested to involve circadian and 24-h activity rhythm disturbances [1,50].…”
Section: -H Activity Rhythms and Other Age-related Diseasesmentioning
confidence: 99%
“…A longitudinal population-based study reported that a lower robustness of the rhythm and a lower amplitude were associated with an increased risk of overall cardiovascular disease, and that a lower mesor was associated with an increased risk of coronary heart disease [70•]. It has also been repeatedly shown that shift work is a risk factor for cardiometabolic disease, such as type 2 diabetes, obesity, and coronary artery disease [50,71,72]; the 24-h activity rhythm has however not been assessed in these studies. Most of these findings have been based on observational studies, making it difficult to determine the underlying mechanisms.…”
Section: Cardio-metabolic Diseasementioning
confidence: 99%
“…These societal changes are thought to negatively impact on patterns of sleep and circadian rhythms across Westernised populations (Kelly et al . ). Also, the use of technology such as video games, mobile devices, television and computers has been reported to negatively influence sleep duration (Ogilvie & Patel ).…”
Section: Why Are People Sleeping Less and How Can We Sleep Better?mentioning
confidence: 97%
“…Biological periodicities occur based on a periodicity in a spectrum of frequencies ranging from milliseconds to years. A circadian rhythm is any biological process that displays an endogenous oscillation of about 24 h [1]. Circadian rhythm is the adaption of our bodies’ biological processes to the day and night cycle.…”
mentioning
confidence: 99%
“…Circadian rhythm is the adaption of our bodies’ biological processes to the day and night cycle. The biological clock is reset daily to synchronize with the exposure to sunlight because our internal clock repeats at around 24 h [1]. Because of the use of artificial light, our internal clock is influenced by multiple factors, including social interactions [1].…”
mentioning
confidence: 99%